ответ:
разделим на 2 каждый член уравнения
\frac{\sqrt{3}}{2}sinx+\frac{1}{2}cos x =\frac{\sqrt{2}}{2}
2
3
sinx+
2
1
cosx=
2
2
\begin{lgathered}\frac{\sqrt{3}}{2}=cos{\frac{\pi}{6}}\\ \frac{1}{2}=sin{\frac{\pi}{6}}\\ sin(x+\frac{\pi}{6})=\frac{\sqrt{2}}{2}\\ x+\frac{\pi}{6} = \frac{\pi}{4}+2\pi n\\ x= -\frac{\pi}{6} + \frac{\pi}{4}+2\pi n\\ x = \frac{\pi}{12}+2\pi n\\ \\ x+\frac{\pi}{6} = \pi-\frac{\pi}{4}+2\pi n\\ x+\frac{\pi}{6} = \frac{3\pi}{4}+2\pi n\\ x=-\frac{\pi}{6} + \frac{3\pi}{4}+2\pi n\\ x = \frac{7\pi}{12}+2\pi {lgathered}
2
3
=cos
6
π
2
1
=sin
6
π
sin(x+
6
π
)=
2
2
x+
6
π
=
4
π
+2πn
x=−
6
π
+
4
π
+2πn
x=
12
π
+2πn
x+
6
π
=π−
4
π
+2πn
x+
6
π
=
4
3π
+2πn
x=−
6
π
+
4
3π
+2πn
x=
12
7π
+2πn
х=183; х=659
Объяснение:
879-х=87*8
879-х=696
-х=696-879
-х=-183
х=183
940-х=843:3
940-х=281
-х=281-940
-х=-659
х=659